Flood and salinity management in the Mekong Delta, Vietnam - Tuan, L.A.; Hoanh, Chu Thai; Miller, F.; Sinh, B.T. (2007)
The great variation in water flow of the Mekong River drives the productivity of the agro- and aqua-ecological systems of the basin, yet also forms a key constraint to intensive production systems. The Mekong River has special ecological and hydrological characteristics that are important to the riparian countries. Floods in the rainy season and salinity intrusion in the dry season form the two main physical problems for sustainable development of the Vietnam Mekong delta. The high floods, as in the year 2000, caused deep inundation and severe damage to infrastructure and production in the delta. Salinity intrusion, which is caused by sea water flowing inland when not enough fresh water flows to the estuaries, also causes problems for production and human health. However, people in the delta consider these processes to be normal natural phenomena and have generally adapted their lives to their presence. This paper offers an analysis of current state of knowledge of the subject drawn from a broad spectrum of nearly 100 publications. From this, the paper then identifies research gaps on floods and saline intrusion in the Mekong Delta to be undertaken in order to better inform a policy debate and decision-making on water resources management to ensure sustainable development and equitable management in the delta and Mekong Basin as a whole.